Absolute calibration of optical power for PDT: Report of AAPM TG140. Issue 8 (23rd July 2013) - Zhu, Timothy C.; Bonnerup, Chris; Colussi, Valdir C.; Dowell, Marla L.; Finlay, Jarod C.; Lilge, Lothar; Slowey, Thomas W.; Sibata, Claudio
Abstract : This report is primarily concerned with methods for optical calibration of laser power for continuous wave (CW) light sources, predominantly used in photodynamic therapy (PDT). Light power calibration is very important for PDT, however, no clear standard has been established for the calibration procedure nor the requirements of power meters suitable for optical power calibration. The purposes of the report are to provide guidance for establishing calibration procedures for thermopile type power meters and establish calibration uncertainties for most commercially available detectors and readout assemblies. The authors have also provided a review of the use of various power meters for CW and pulsed optical sources, and provided recommended temporal frequencies for optical power meter calibrations and guidance for routine quality assurance procedure.